Global Leadership or Self-Governance: The Basic Laws of Governance - Dimitar Tchurovsky (Cadmus, 2024)
In terms of its complexity, modern society is comparable to the intricacy of the human brain. Undoubtedly, the global leadership of a system with thousands of subsystems is a real challenge for humanity. Governance is the process of making decisions and solving national, regional and global problems where multiple factors are taken into account. They can be divided into two groups—subjective and objective. Subjective factors include ideologies, geopolitics, the competence and intelligence of the ruling elite, the role of money, public opinion and many others that are the fruit of reason. These factors are complicated by the presence of objective factors such as the level of development of society, a wide range of national interests, the state of the economy, cultural, ethnic and racial characteristics, etc. Obviously, the consideration of all these features is not within the capabilities of individual and collective intelligence. Until now, about 200 forms of government have been used for governance in different historical eras and specific conditions, but for the future society, a governing mechanism or a form of government qualitatively different from those already used is needed. This problem can be solved by a transition from ideologies to a scientifically based vision of society. To develop such a vision, it is necessary to reveal the basic laws determining the structure and functioning of society. The basic laws of governance are only a part of them.